THE MEDIA EFFECT ON THE IMPULSIVE BUYING BEHAVIOR WITH FINANCIAL LITERACY AS A MODERATING VARIABLE - Oktaviana, Yasinta
The rapid growth of online food delivery applications (OFDA) in Indonesia, coupled with the increasing digital media exposure of younger generations, has raised concerns about impulsive buying behavior and its financial implications. This study investigates the effect of media on impulsive buying behavior towards OFDA among Generation Z (aged 17-27) and Millennials (aged 28-43) in Indonesia, with financial literacy as a moderating variable. The research employed a quantitative approach, collecting data from 439 Generation Z and 407 Millennial respondents. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and MultiGroup Analysis (MGA), the study examined relationships between variables and compared effects across generational groups. Results indicate that media has a significant positive impact on impulsive buying behavior towards OFDA for both Generation Z and Millennials, with a stronger effect observed among Millennials. Financial literacy was found to significantly moderate this relationship for Millennials and the combined group, but not for Generation Z. These findings highlight the crucial role of media in influencing impulsive buying behavior towards OFDA, particularly among Millennials. The study contributes to understanding how different generations respond to media influences in the context of online food ordering, and how financial literacy interacts with these factors. Recommendations include developing targeted media literacy programs for Generation Z and integrating media literacy into financial education for Millennials. Educational institutions and government bodies are advised to develop differentiated financial and media literacy programs for each generation, recognizing their distinct characteristics in OFDA consumption. This research contributes to the understanding of media's impact on consumer behavior in the digital age, particularly in the context of OFDA in Indonesia, and highlights the complex role of financial literacy in moderating this relationship across different generational groups.